2019
DOI: 10.1017/cjn.2019.162
|View full text |Cite
|
Sign up to set email alerts
|

P.062 Burden of illness of spinal muscular atrophy (SMA): an update

Abstract: Background: In this retrospective claims analysis, real-world healthcare resource use (HRU) and costs among SMA type 1 (SMA1) patients were assessed. Methods: SMA1 patients were identified from Symphony Health’s Integrated Dataverse® (09/01/2016–08/31/2018). The study period spanned from the index date (date of first SMA1 diagnosis after nusinersen approval [12/23/2016]) until death/end of available data. HRU and costs per-patient-per-year (PPPY; 2018USD) were described during the study period for all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A total of 34 publications, comprising 32 unique studies of patients with SMA that met all eligibility criteria were identified in the original search. Two conference abstracts were linked [48,49], and one conference abstract and one manuscript were linked [50,51]. However, these abstracts and manuscripts contained unique data; therefore, all were included as discrete publications.…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 34 publications, comprising 32 unique studies of patients with SMA that met all eligibility criteria were identified in the original search. Two conference abstracts were linked [48,49], and one conference abstract and one manuscript were linked [50,51]. However, these abstracts and manuscripts contained unique data; therefore, all were included as discrete publications.…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
“…The final list of 51 publications comprised 27 full-text publications [50,, 23 conference abstracts [48,49,51,52,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] and one slide deck [98]. Cost and resource use data were reported in 23 publications [48, 50, 53-57, 60, 61, 68, 70-77, 79, 84, 85, 92, 98].…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
See 2 more Smart Citations